Revitalizing Creative Industries: A Strategic Approach to Bolstering Buleleng Regency's Economy Amidst the COVID-19 Pandemic - Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini; Ni Ketut Sari Adnyani (Journal of Judicial Review, 2023)
This study investigates the impact of the COVID-19 pandemic on micro, small, and medium enterprises (MSMEs) in Buleleng Regency, particularly in the creative industry sector. It aims to (1) analyze the status of MSME-based creative industries during the pandemic, (2) identify the challenges faced by these enterprises, and (3) propose economic policy strategies to strengthen them. Findings reveal that (1) the number of MSME-based creative industries in Buleleng Regency increased between 2019 and 2022. However, they encountered issues such as limited access to capital, lack of business formalization, human resource constraints, technology underutilization, suboptimal marketing and promotional efforts, and production challenges. (2) During the pandemic, these businesses faced obstacles like limited capital for owners, scarcity of raw materials and production equipment, bookkeeping issues, marketing constraints, managerial deficiencies, limited human resource capabilities, and difficulties in product distribution. (3) To bolster MSME-based creative industries during the pandemic, a multi-pronged economic policy strategy is proposed. This includes instilling local pride in using MSME products, enhancing product packaging, and organizing MSME groups based on business scale with the involvement of a curation team to identify businesses suitable for broader exposure.